Pelatihan Sistem Pengendalian Internal Keuangan untuk Mendukung Pengelolaan Usaha Desa Wisata Berkelanjutan - Cahyaningsih; Saraswati, Rr Sri; Pratomo, Dudi; Muhaemi, Enung (Jurnal Atma Inovasia, 2026)
Tenjolaya Village in Pasirjambu District, Bandung Regency, has great potential as a tourist village based on agro- and ecotourism. With an area of 65.68 km² and a population of 15,986, Tenjolaya has attractions such as natural mountain tourism, tea plantations, coffee plantations, waterfalls, and culinary specialties such as kalua jeruk. However, managing this potential still faces obstacles due to the lack of an integrated management ecosystem, particularly in terms of administration and finance. One of the main problems is the low understanding of internal control among administrators and business actors, including financial recording systems, profit sharing, and fair payroll. This community service activity aims to provide understanding and skills to Tenjolaya residents regarding the importance of internal control and a simple financial management system to support the sustainability of the tourist village. Through interactive lectures, focus group discussions (FGDs), and business management simulations (homestays and tourist ticket management), participants are trained to understand the principles of internal control, transaction recording, and a transparent payroll system. The results of the activity showed a significant increase in the level of internal control literacy of residents, which is expected to be the foundation for creating a healthy, accountable and competitive tourism village ecosystem.